Menopause modified the association of blood pressure with osteoporosis among gender: a large-scale cross-sectional study - Jin, Haidong; Zhao, Hongfei; Jin, Sufan; Yi, Xianhong; Liu, Xiaotian; Wang, Chongjian; Zhang, Gongyuan; Pan, Jun (Frontiers in Public Health, 2024)
 The evidence on blood pressure and bone health was limited, especially in rural areas. The possible reasons for blood pressure and bone metabolism were unclear. Might blood pressure influence the risk of osteoporosis in rural populations? If there is a sex difference in the association in areas with limited resources? There was a positive association between blood pressure with osteoporosis risk in areas with limited resources. Menopause may be the key to gender difference. The investigation was focused on moderate and low-income citizens. The levels of blood pressure and osteoporosis were significant correlation in women. Menopause modified the association between blood pressure and osteoporosis. The divergent blood pressure proxies may be the potential indicators for screening high osteoporosis risk among postmenopausal women in rural areas.